Steam reforming of ethanol, acetaldehyde, acetone and acetic acid: Understanding the reaction intermediates and nature of coke. (16th January 2023) - Bkangmo Kontchouo, Félix Mérimé; Shao, Yuewen; Zhang, Shu; Gholizadeh, Mortaza; Hu, Xun
Graphical abstract: Highlights: Dissociative adsorption of acetic acid forms ketene via dehydration but not cracking. Ethanol absorption on Ni/KIT-6 forms species with CH and CC as coke precursors. Aldol-condensation of strongly adsorbed acetone is a major route of coke formation. Acetaldehyde polymerizes even at 100 °C, forming polymeric coke of amorphous form. Coke from ethanol/acetone/acetic acid is catalytic type of highly aromatic nature. Abstract: The small aliphatic organics like ethanol, acetaldehyde, acetone and acetic acid are frequently used as feedstocks for hydrogen production via steam reforming. These organics have distinct functionalities, which might result in formation of different reaction intermediates and coke. This was investigated in this study with Ni/KIT-6 as a catalyst under normalized conditions. The results indicated that dehydration to ketene but not cracking was major route for dissociative adsorption of acetic acid on Ni/KIT-6 from 100 °C. Thermally stable CH and CC in alkenes, formed via dehydration of ethanol and aromatization of acetone/intermediates via bimolecular Aldol-condensation, were important precursors of coke in ethanol and acetone reforming. Although acetone strongly adsorbed on Ni/KIT-6, it did not polymerize to heavy oxygen-containing organics that were difficult to be gasified with steam. In comparison, the similar strong adsorption of acetaldehyde led to rapid polymerization even at 100 °C, forming the polymeric coke of highly aliphatic nature. The coking tendency in reforming followed the order: acetone > acetic acid > ethanol > acetaldehyde. Nevertheless, the amorphous form of coke in acetaldehyde reforming led to the rapid deactivation of Ni/KIT-6. The coke in ethanol, acetone and acetic acid reforming were mainly the catalytic type with the highly aromatic nature, high carbon crystal crystallinity, high thermal stability, high resistivity towards oxidation and the carbon nanotube morphology. Nevertheless, the varied reaction intermediates involved in reforming of these varied feedstock also formed the coke of some unique features.